Glucagon-like peptide-1 exerts anti-inflammatory effects on mouse colon smooth muscle cells through the cyclic adenosine monophosphate/nuclear factor-κB pathway in vitro - Al-Dwairi A; Alqudah TE; Al-Shboul O; Alqudah M; Mustafa AG; Alfaqih MA (Dove Medical Press, 2018)
Ahmed Al-Dwairi,1 Tamara E Alqudah,1 Othman Al-Shboul,1 Mohammad Alqudah,1 Ayman G Mustafa,2 Mahmoud A Alfaqih1 1Department of Physiology and Biochemistry, Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Anatomy, Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan Background: Intestinal smooth muscle cells (SMCs) undergo substantial morphological, phenotypic, and contractile changes during inflammatory bowel disease (IBD). SMCs act as a source and target for different inflammatory mediators, however their role in IBD pathogenesis is usually overlooked. Glucagon-like peptide-1 (GLP-1) is an incretin hormone reported to exert multiple anti-inflammatory effects in different tissues including the gastrointestinal tract through various mechanisms. Aim: The aim of this research is to explore the effect of GLP-1 analog exendin-4 on the expression and secretion of inflammatory markers from mouse colon smooth muscle cells (CSMCs) after stimulation with lipopolysaccharide (LPS). Materials and methods: Freshly isolated CSMCs from male BALB/c mice were cultured in DMEM and treated with vehicle, LPS (1 µg/mL), LPS+exendin-4 (50 nM), or LPS+exendin-4 (100 nM) for 24 h. Expression of inflammatory cytokines was then evaluated by antibody array membrane. Results: CSMCs showed basal expression of several cytokines which was enhanced with the induction of inflammation by LPS. However, exendin-4 (50 and 100 nM) significantly (p<0.05) reduced the expression of multiple cytokines including tumor necrosis factor-α (TNF-α), interleukin-1α (IL-1α), T cell activation gene-3 (TCA-3), stromal cell-derived factor-1 (SDF-1), and macrophage colony stimulating factor (M-CSF). To confirm these results, expression of these cytokines was further assessed by enzyme-linked immunosorbent assay and real-time polymerase chain reaction and similar results were also observed. Moreover, secretion of TNF-α and IL1-α into the conditioned media was significantly downregulated by exendin-4 when compared to LPS-treated cells. Furthermore, LPS increased NF-κB phosphorylation, while exendin-4 significantly reduced levels of NF-κB phosphorylation. Conclusion: These data indicate that GLP-1 analogs can exert significant anti-inflammatory effects on CSMCs and can potentially be used as an adjunct treatment for inflammatory bowel conditions. Keywords: GLP-1, inflammation, inflammatory bowel disease, smooth muscle